Anti-Corruption Education Based on Local Wisdom: An Analysis of Anti-Corruption Management Values in the Local Wisdom of the Pasemah and Serawai Communities of Bengkulu - Satria, Irwan; Akbarjono, Ali; Budrianto; Syaputra, Een (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
Bengkulu society has an extraordinarily rich local wisdom that can be utilized for character building, including anti-corruption. This study aims to analyze anti-corruption values ​​in the local wisdom of Bengkulu society, especially the Pasemah and Serawai communities. The study was conducted using a qualitative case study method. Data were collected through interviews, observations and documentation analysis. Data were analyzed using an interactive model. The results of the study indicate that: 1) Anti-corruption values ​​in the local wisdom of the Pasemah and Serawai Bengkulu communities can be found in several objects/cultures, especially in oral traditions (traditional expressions, folk prose stories, and folk songs), rites or traditions and customs, and traditional games or sports; 2) Anti-corruption values ​​contained in oral traditions are the values ​​of honesty, responsibility, discipline, hard work, simplicity, independence, caring and fairness. Of the eight values, the two most dominant values ​​are honesty and simplicity. Meanwhile, the anti-corruption values ​​contained in traditions or rites are the values ​​of care and responsibility. As for the anti-corruption values ​​contained in traditional games or sports are honesty, discipline, hard work, and independence. Thus, it can be concluded that the local wisdom of the Pasemah and Serawai communities is very potential to be used as the basis for anti-corruption education.